ANALISIS PENGARUH KEPUASAN PENUMPANG ANGKUTAN MASSAL BERBASIS JALAN PERKOTAAN TERHADAP LOYALITAS PENUMPANG (STUDI KASUS : TRANS METRO DELI) - Sekula BR Sinuraya; M. Ridwan Anas; Emma Patricia Bangun (Syntax Corporation Indonesia, 2023)
Road-based mass transit systems or commonly referred to as Bus Rapid Transit (BRT) are currently experiencing quite rapid development in various countries including Indonesia. At the end of 2020 the Government has inaugurated urban road-based mass public transportation with the Buy The Service (BTS) Service Scheme in 5 (five) major cities including the city of Medan. Evaluation or strategy must continue to be carried out so that this BTS mode can continue to be sustainable. One of the steps that can be taken is to examine the level of satisfaction and loyalty of current users to continue using the BTS mode. This underlies this research to analyze the level of passenger satisfaction of the Trans Metro Deli Bus and to analyze the effect of passenger satisfaction on the loyalty of the Trans Metro Deli Bus passengers. The Importance Performance Analysis (IPA) Method is used to analyze the satisfaction level of Trans Metro Deli Bus passengers because this method can be used to evaluate and design management from the results of the analysis of service user perceptions regarding the suitability between expectations and quality received. While the Partial Least Square – Structural Equation Modeling (PLS – SEM) Method is used to analyze the effect of passenger satisfaction on passenger loyalty because this method can be used to estimate model relationships. This analysis method uses Smart PLS software. Through measurements using the IPA method, the results show that the highest level of passenger satisfaction is found in the safety attribute (92.59%), then the safety attribute (90.54%), and comfort (91.11%). All three are included in the achievement quadrant that must be maintained, and the attributes of equality (87.24%) and regularity (87.74%) are included in the low priority quadrant while the affordability attribute (84.79%) is included in the quadrant which is the main priority for improvement . Meanwhile, if analyzed per each corridor, in the Medan Tuntungan – Merdeka Square corridor, the affordability attribute is included in the low priority quadrant because in terms of quality it is still low, but expectations are also low. And when analyzed on a job basis, the regularity attribute is included in the top priority to be improved. The results of the analysis of the effect of passenger satisfaction on passenger loyalty using the PLS-SEM method concluded that the effect of passenger satisfaction on passenger loyalty was significant with an influence value of 0.647 and the direction of the relationship between the two variables was positive.